A note on the exclusion principle - Paolo Bertoletti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2005)
According to the so-called Exclusion Principle (introduced by Baye et alii, 1993), it might be profitable for the seller to reduce the number of (fullyinformed) potential bidders in an all-pay auction. We show that the Exclusion Principle does not apply if the seller regards the bidders' private valuations as belonging to the class of identical and independent distributions with a monotonic hazard rate.
Keywords: D44; D72; D82; 330; all-pay auctions; Exclusion Principle; monotonic hazard rate; economic theory of lobbying; Auktionstheorie; Interessenpolitik